Teter Rock - Sandy Dorsey (Symphony in the Flint Hills, 2014)
Teter Rock sits alone atop one of the highest peaks in the Flint Hills at an elevation of 1,634 feet. The view from the peak, locally known as Texaco Hill, is an unmatched tranquil panoramic view of the surrounding tallgrass prairie. To the uninitiated, “Teter Rock” may seem a name that describes the precarious monolith, but it is anchored deeply into the ground.
Keywords: Teter rock; teterville; monolith; geology; rock; landscape; stone; oil boom; oil wells; John Teter; cattle; ranch; Arapahoe Pipeline Company; large; Cassoday